Potensi Pengembangan Koperasi Pegawai Negeri Syariah RSUD Prof. DR. M. A Hanafiyah SM Batusangkar dengan Menggunakan Analisis SWOT - Afif, Rifqul (UIN Imam Bonjol Padang, 2019)
This study aims to determine the potential development of Islamic civil servant cooperatives in RSUD Prof. DR. M.A Hanafiah BC Batusangkar using SWOT analysis. The analysis phase used is: using the EFAS and IAS matrices, the SWOT / TOWS matrix, the SPACE matrix, the IE matrix and the decision making stage using the QSPM matrix. Based on the results of the stages of analysis, it can be concluded: Potential development of the Sharia Supervisory Cooperative at RSUD Prof. Dr. MA Hanafiah BC Batusangkar using SWOT analysis. The results of the SWOT analysis are 9 alternative strategies, as fol- lows: 1) Increasing business unit capital, especially savings and loans busi- ness, 2) Utilizing business legality to establish cooperation in connection with Law 20 of 2008 concerning MSMEs, 3) Increasing cooperation with govern- ment and private sector, 4) Hold training in accordance with needs, 5) Always coordinate with Supervisors, Managers, and employees, 6) Perform updates in terms of business units and services to be superior to competitors, 7) Improve performance of Supervisors, Managers, and Employees for the next step re- garding progress and decline of cooperatives, 8) Increasing the quality of HR capabilities regarding sharia contracts, and 9) Utilization of technology for bookkeeping and others. The selection of alternative strategies with the QSPM method shows the alternative strategies that are of interest to the respondents. The alternative strategy with the highest TAS value is a strategy that needs to be implemented in advance by the Sharia State Supervisory Cooperative of RSUD Prof. Dr. MA Hanafiah BC Batusangkar. The results from table 4.10 show that the highest TAS value is improving the performance of Supervisors, Managers, and Employees for the next step regarding the progress and decline of cooperatives